Effectiveness of Tai Chi on fibromyalgia patients: A meta-analysis of randomized controlled trials. (October 2019) - Cheng, Ching-An; Chiu, Ya-Wen; Wu, Dean; Kuan, Yi-Chun; Chen, Sheng-Ni; Tam, Ka-Wai
Highlights: Tai Chi is effective in the management of fibromyalgia-related syndromes. Tai Chi reduce FIQ score, pain score, fatigue and depression significantly. Sleep quality and quality of life can be enhanced by Tai Chi. Tai Chi is recommended as an alternative to standard care for fibromyalgia patients. Abstract: Objective: To identify empirical evidence on the effectiveness of Tai Chi in treating fibromyalgia (FM). Method: We conducted a systematic review and meta-analysis of randomized controlled trials (RCTs) to compare the effectiveness of Tai Chi and standard care or conventional therapeutic exercise in patients with FM. PubMed, Medline, and Physiotherapy Evidence Database were searched for relevant studies published before May 2019. Treatment effectiveness was evaluated using the fibromyalgia impact questionnaire (FIQ), and the total score, pain score, sleep quality index, fatigue, depression, and quality of life were assessing among the patients. Results: Six RCTs with 657 patients were included. Results of our meta-analysis indicated that Tai Chi exerts significant positive effects on reducing the total FIQ score at 12–16 weeks (standard mean difference [SMD]: −0.61; 95% confidence interval [CI]: −0.90 to −0.31) and pain score (SMD: −0.88; 95% CI: −1.58 to −0.18), improving sleep quality (SMD: −0.57; 95% CI: −0.86 to −0.28), relieving fatigue (SMD: −0.92; 95% CI: −1.81 to −0.04), alleviating depression (SMD: −0.49; 95% CI: −0.97 to −0.01), and enhancing quality of life physically (SMD: 6.21; 95% CI: 3.18–9.24) and psychologically (SMD: 5.15; 95% CI: 1.50–8.81). Conclusion: Tai Chi exerts significantly greater effects on patients with FM than standard care; therefore, we suggest that Tai Chi can be used as an alternative treatment. However, more large-scale, high-quality, and multicenter trials are required to provide stronger evidence on the effectiveness of Tai Chi, as an alternative to aerobic exercise, compared with conventional therapeutic exercise.